An application of impact calculation method in transportation - Wangai, Agnes; Kale, Utku; Kinzhikeyev, Sergey (Transport, 2020)
Forecasted/projected rise of impacts in modes of transportation has necessitated a new rethinking of the evaluation of total impact. While most researchers deal with defined parts (like environmental impact) of the total impact. The total impact calculation methodology includes: (1) analysis of all the impacts (environmental impact, safety and security, costs, cost benefits and sustainability), (2) evaluation on the transportation system level, (3) as their total value (including all the related sub-systems and elements, i.e. transport infrastructure, transport flow control), (4) generation of total impact index. Such an index might be called as transport total sustainability index. The paper defines the Total Impact Performance Index (TIPI) evaluating the total impact in the form of generalized (summarized) costs, specifies its calculation methodology, develops a simplified Excel based calculation methods. It aims to demonstrate the applicability of this methodology, which involves evaluation of impacts in more detailed forms, two parts calculation methods namely impact of road transport safety aspects and impact of the railway transport. Finally, some selected results of the applied new index calculation and developed methodology are introduced and analysed.